Estimating the value of Urban Green Space: A hedonic pricing analysis of the housing market in Cologne, Germany - Jens Kolbe; Henry Wüstemann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
Urban Green Space (UGS) such as parks and forests provide a wide range of environmental and recreational benefits. One objective in the conservation efforts of UGS is to analyse the benefits associated with UGS in order to make them more visible and to provide support for landscape planning. This paper examines the effects of UGS on house prices applying a Hedonic Pricing Method (HPM). The data set contains over 85,046 geo-coded apartment transactions for the years 1995- 2012 and contains information on three intrinsic variables of the real estate (e.g. transaction price, floor area and age). In order to examine the capitalization of UGS in real estate prices we further incorporate crosssection geo-coded data for the different types of UGS: forests, parks, farmland and fallow land drawn from the European Urban Atlas (EUA) of the European Environment Agency for the year 2006. In order to control for additional open space categories we further incorporated geo-coded data on water bodies and fallow land. Using a Geographical Information System (GIS) we calculated the coverage of UGS in pre-defined buffers around households as well as the distance in a continuous fashion (Euclidian distance) between UGS and the households. Our results show a capitalization of UGS in real estate prices but the effect of the structural variables is higher. We found a positive price effect of parks, forests and water and an inverse relation between the price variable and the presence of fallow land and farmland.
Keywords: R31; C14; Q50; 330; Urban Green Space (UGS); Open Space; Hedonic Pricing Method (HPM); GISAnalysis